Catalytic activity of Pt-Ni nanoparticles supported on multi-walled carbon nanotubes for the oxygen reduction reaction. (28th December 2016) - Rosado, G.; Verde, Y.; Valenzuela-Muñiz, A.M.; Barbosa, Romeli; Miki Yoshida, M.; Escobar, B.
Abstract: The synthesis and characterization of Pt–Ni nanoparticles with different Ni:Pt atomic ratios and supported on multi-walled carbon nanotubes (MWCNTs) for oxygen reduction reaction (RRO) is investigated. The crystal structure and the elemental analysis of Pt–Ni/MWCNTs nanocatalysts are characterized by X-ray diffraction (XRD) and energy dispersive X-ray spectroscopy (EDS), respectively. The morphology of these nanocatalysts is observed by transmission electron microscopy (TEM). The results reveal that Pt–Ni nanocatalysts with a nanoparticle size ranging from 6 to 7 nm are immobilized on the surface of MWCNTs. The kinetics and mechanism of the ORR were analyzed in a 0.5 M H2 SO4 solution. The cyclic voltammetry response indicates that PtNi/MWCNTs catalyst displays a higher performance than Pt/MWCNT, which may be due to the alloy of Ni species in PtNi systems, demonstrating that they are promising materials for using in fuel cells. Highlights: Pt–Ni alloy nanoparticles were successfully synthesized by chemical reduction. The type of crystalline structure exhibited by both Pt and Ni is face-centered cubic. XRD and HRTEM analysis of the nanoparticles indicated that have alloy configuration. The Pt–Ni synthesized materials showed good electrocatalytic properties towards the ORR. FTIR analysis does not show transmittance bands related to PVP vibrations.